RHODOCOCCUS PYRIDINIVORANS STRAIN TPIK, A NITRILE-DEGRADING BACTERIUM ISOLATED FROM TAILING POND OF ANTAM GOLD MINING INDUSTRY , PONGKOR - Sulistinah, Nunik; Riffiani, Rini; Sunarko, Bambang (LIPI Press, 2015)
Nitriles are widely manufactured and extensively used by chemical industries as synthesis intermediates. Although these compounds are generally highly toxic, due to their cyano functional group, they can be used by some microorganisms as carbon and/or nitrogen sources. Nitrilase catalyzes the direct cleavage of nitriles to the corresponding acids and ammonia, where as nitrile-hydratase catalyzes the hydratation of nitriles to amides. Applications of these nitrile-converting enzymes are now increasingly recognized for the production of several pharmaceutically important compounds and fine chemicals. By virtue of their capability to eliminate highly toxic nitriles, the enzymes also play a significant role in protecting the environment. Accordingly, it is very important to find microorganisms that have a great capacity to utilize or degrade nitriles. Recently, a bacterial isolate TPIK which shows high nitrile degrading activity has been isolated. The strain was isolated from tailing pond of gold mine activity by selective enrichment methods. TPIK was shown to be capable of degrading high concentrations of nitrile (up to approx. 1 M acetonitrile). Colonies of TPIK are light orange in colour and have irregularly round wrinkles. The cells of TPIK are non-spore-forming, non motile and Gram-positive, but are Gram-variable in old cultures. The cells are rods and brached fillaments during the early growth phase and then fragmented into short rods and cocci. The taxonomic position of TPIK was clarified using molecular genetic methods. The phylogenetic tree showed that bacterial isolate TPIK falls within an evolutionary radiation comprising Rhodococcus species and is most closely related to the type strain of Rhodococcus pyridinivorans, sharing 99% 16S rDNA similarity. To the best of our knowledge, this was the first time that Rhodococcus pyridinivorans has been described as containing nitrile-degrading enzymes. Usually, this bacterial strain has been studied for its ability to degrade carcinogenic compounds, like pyridine.